SAT0502 High Participation in School and Physical Education in Children in a Nordic Juvenile Idiopathic Arthritis Cohort. (9th June 2015) - Nordal, E.B.; Berntson, L.; Aalto, K.; Fasth, A.; Herlin, T.; Nielsen, S.; Peltoniemi, S.; Zak, M.; Rygg, M.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is an umbrella term for chronic childhood arthritis. Even in the era of modern efficient treatment, many children with JIA experience difficulties attending daily life activities. Objectives: The aim of the study was to analyse school attendance and participation in physical education (PE) in a cohort of Nordic children with JIA in a population-based setting. Methods: Consecutive cases of JIA from defined geographical areas of Denmark, Finland, Sweden and Norway with disease onset in 1997 to 2000 were prospectively included in a population-based design. Clinical data, school attendance and participation in PE during the last two months were registered at study visits six months and >7 years after disease onset. Danish participants did mostly not fill in information on school attendance and PE and were therefore excluded. Results: Of 347 children with long-term follow-up, information on recent participation in school and PE was available in 239 children. Among these children, 65.7% were female, median age at onset of disease was 4.3 years and 49.8% had oligoarticular JIA the first 6 months after onset. Mean age at last visit was 12.5 (IQR 10.4-15.9) years. Eight years after onset 82.4% reported no school absence, and 6.7% reported >3 days during the last two months due to JIA. Full participation in PE was reported by 79.9%, partly by 17.2%, and 2.9% reported no participation. Lower school attendance and participation in PE were significantly associated with higher number of active joints, and higher CHAQ scores. There were no gender differences in school attendance, but significantly fewer girls than boys participated fully in PE (p=0.01). There were no age differences regarding school attendance or participation in PE. There were no significant differences in school attendance between JIA categories, but significantly fewer children participated fully in PE in the enthesitis-related arthritis (ERA) (65.0%) and the undifferentiated (62.5%) categories, while participation was highest in the oligoarticular persistent category (92.4%). Conclusions: School attendance and participation in PE was generally high >7 years after onset in the Nordic JIA cohort. Fewer girls than boys participated fully in PE. Notably, lower participation was also found among children with ERA, where physical activity is particularly recommended. Disclosure of Interest: None declared